Inscriptions on the pedestal of a Jain statue - Temples of India Project Team (Jio Institute, 2024)
Inscriptions on the pedestal of a Jain statue in the Jain Temple remains at Arthuna. A cursory glance at the orthography and script of the inscriptions indicates that they belong to the sixteenth century, probably recording the consecration of these statues.